2004
DOI: 10.1055/s-2004-861495
|View full text |Cite
|
Sign up to set email alerts
|

β-Thalassemia Is a Modifying Factor of the Clinical Expression of Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is a codominant disorder due to a variety of mutations of the low-density lipoprotein (LDL) receptor gene that result in an elevation of plasma LDL-cholesterol (LDL-C). Plasma levels of LDL-C show large interindividual variation even in subjects carrying the same mutation of the LDL receptor gene. This variability may be due to genetic factors (modifier genes). Several surveys indicate that the overall contribution of common polymorphisms of modifier genes (such as the genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…Moreover, the LDL lowering effect associated with the b-thalassemia trait may be also related to the activation of the monocyte/macrophage system in spleen, liver, and bone marrow with the generation of several inflammatory cytokines, which at least in vitro in HepG2 cells, increase LDLR gene expression and reduce the assembly of apoB-containing lipoproteins. 38 In addition, a recent meta-analysis of 8 case-control studies (involving 9479 individuals) showed that the b-thalassemia trait was associated with a reduced risk of arterial cardiovascular and cerebrovascular events in male patients (odds ratio 0.39; confidence interval 0.24-0.62). 39 In agreement with the aforementioned findings, the LDL-C level was ,25 th percentile in proband's mother and ,15 th percentile in proband's grandfather with respect to the distribution of LDL-C level in gender-and age-matched normal individuals of the Italian population.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the LDL lowering effect associated with the b-thalassemia trait may be also related to the activation of the monocyte/macrophage system in spleen, liver, and bone marrow with the generation of several inflammatory cytokines, which at least in vitro in HepG2 cells, increase LDLR gene expression and reduce the assembly of apoB-containing lipoproteins. 38 In addition, a recent meta-analysis of 8 case-control studies (involving 9479 individuals) showed that the b-thalassemia trait was associated with a reduced risk of arterial cardiovascular and cerebrovascular events in male patients (odds ratio 0.39; confidence interval 0.24-0.62). 39 In agreement with the aforementioned findings, the LDL-C level was ,25 th percentile in proband's mother and ,15 th percentile in proband's grandfather with respect to the distribution of LDL-C level in gender-and age-matched normal individuals of the Italian population.…”
Section: Discussionmentioning
confidence: 98%
“…Presently, the clinical implications of this anemia-associated hypocholestrolemia are unknown. It has been suggested that, in b-thalassemia, hypocholesterolemia is a modifying factor underlying the clinical expression of familial hypercholesterolemia [12]. Some previous data suggest that the incidence of coronary artery disease is lower in patients with b-thalassemia compared with controls [9].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of the hypocholesterolemia in these settings remains obscure, although several mechanisms have been proposed: plasma dilution due to anemia, increased cholesterol requirement associated with erythroid hyperplasia, macrophage system activation with cytokine release, increased cholesterol uptake by the reticuloendotial system, and liver injury secondary to iron overload [2,3]. Few small uncontrolled studies have also suggested a lower incidence of coronary artery disease in anemic patients with b-thalassemia and hereditary spherocytosis [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The present plasma cholesterol pattern is not confined to β-TI but extends to all β-thalassemic syndromes [11,12]. We hypothesize a promotion of vascular damage in a milieu of hemostatic abnormalities, oxidative stress, and immunomodulation, each of which has been constantly demonstrated among thalassemic patients, whether regularly transfused or not [1,5,6,9,12].…”
Section: Discussionmentioning
confidence: 99%